Simplifying 3 - (4x - 5) + 6, we can distribute the negative sign to both terms inside the parentheses:
3 - 4x + 5 + 6
Then we can combine like terms:
(3 + 5 + 6) - 4x
This simplifies to:
14 - 4x
Simplify 3 - (4x - 5) + 6.
5 answers
wrong
I apologize for my mistake. Let's start over and simplify the expression correctly.
To simplify 3 - (4x - 5) + 6, we first simplify the expression inside the parentheses:
3 - (4x - 5) + 6
= 3 - 4x + 5 + 6
Next, we combine like terms:
= (3 + 5 + 6) - 4x
= 14 - 4x
So, 3 - (4x - 5) + 6 simplifies to 14 - 4x.
To simplify 3 - (4x - 5) + 6, we first simplify the expression inside the parentheses:
3 - (4x - 5) + 6
= 3 - 4x + 5 + 6
Next, we combine like terms:
= (3 + 5 + 6) - 4x
= 14 - 4x
So, 3 - (4x - 5) + 6 simplifies to 14 - 4x.
simplify 3-(4x-5)+6
To simplify 3 - (4x - 5) + 6, we can first simplify the expression inside the parentheses by distributing the negative sign:
3 - (4x - 5) + 6
= 3 - 4x + 5 + 6
Next, we combine like terms:
= 3 + 5 + 6 - 4x
= 14 - 4x
So, 3 - (4x - 5) + 6 simplifies to 14 - 4x.
3 - (4x - 5) + 6
= 3 - 4x + 5 + 6
Next, we combine like terms:
= 3 + 5 + 6 - 4x
= 14 - 4x
So, 3 - (4x - 5) + 6 simplifies to 14 - 4x.